Society - Water - Technology : (Springer Open, 2016)
This book presents the results of the Interdisciplinary Research Group "Society – Water – Technology" of the Berlin-Brandenburg Academy of Sciences and Humanities. It describes interdisciplinary evaluation criteria for major water engineering projects (MWEPs) and portrays an application to the Lower Jordan Valley (Middle East) and the Fergana Valley (Central Asia). Both areas are characterised by transboundary conflicts, by challenges due to demographic and climate change and by political and societal pressures. Based on the findings, the book provides recommendations for science and political decisions makers as well as for international financing institutions. In addition, it outlines research gaps from an interdisciplinary perspective.